Fibre-volume-fraction measurement of carbon fibre reinforced thermoplastic composites using thermogravimetric analysis. Issue 1 (January 2019) - Mohsin, M.A.A.; Iannucci, L.; Greenhalgh, E.S.
Abstract: The fibre-volume-fraction (FVF) measurement of fibre-reinforced polymers (FRPs) is crucial in understanding and characterising their mechanical performance. To date, there has not been a standardised, labour-efficient method in determining the FVF of a non-crimp fabric (NCF) carbon reinforced thermoplastic composites (CFRTPs). An alternative method such as thermogravimetric analysis (TGA) has merely been commonly used for carbon-fibre reinforced thermosets (CFRTSs) and glass-fibre reinforced thermosets (GFRTSs). Therefore, this paper reports a range of macro TGA measurements of the constituent materials of two NCF CFRTPs; (i) T700 carbon/polyamide6.6 (PA6.6) and (ii) T700 carbon/polyphenylene sulphide (PPS). The TGA measurements were performed using two different purge gases (air and nitrogen) and the mass degradation with respect to time, temperature and atmospheres were recorded and discussed. Additionally, fractographic analysis on the fibres was carried out to scrutinise and further discuss the findings following the TGA. It was concluded that TGA provided a suitable and reliable alternative method to measure the FVF of CFRTPs.